2015
DOI: 10.1007/s00520-015-3007-z
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in the terminal stage of cancer

Abstract: Polypharmacy still is a problem in the large majority of patients with terminal cancer. Further studies should be focused on the patients' quality of life, drug interactions, and adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 23 publications
4
37
0
8
Order By: Relevance
“…Our results enhance previous studies demonstrating that patients are poly‐medicated even during their last period of life …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results enhance previous studies demonstrating that patients are poly‐medicated even during their last period of life …”
Section: Discussionsupporting
confidence: 89%
“…Our results enhance previous studies demonstrating that patients are poly-medicated even during their last period of life. 16 We included only patients defined by their medical authorities as having very limited life expectancy. Unless promised unrealistic hopes for cure or significant life extension, these patients usually seek comfort and symptomatic relief.…”
Section: Addressing Our Study's Main Findingsmentioning
confidence: 99%
“…27 In one chart review of 100 patients with advanced cancer, 95% had polypharmacy in the week before death. 28 In oncology settings, the presence of polypharmacy has been associated with higher numbers of comorbidities, increased use of inappropriate medications, worse performance status, frailty syndrome, poor physical function and poor survival. 24, 29, 30 …”
Section: Introductionmentioning
confidence: 99%
“…The reason for high consumption of preventive drugs in the aforementioned study was stated to be the lack of coordination between the healthcare service providers in the primary and secondary levels. Moreover, other studies identified opioids, psychoactive drugs (Kierner et al, 2016), morphine and other painkillers, as well as antiemetic drugs (Nauck et al, 2004) as the most frequently-used medications in the patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous definitions have been proposed such as concurrent use of multiple medications, use of incompatible medications, or inadequate consumption of medication. A number of studies have defined the polypharmacy as the simultaneous consumption of more than four or five medications (Maggiore et al, 2010;Kierner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%